Ghuluw dalam Akidah Islam: Satu Pengenalan Ringkas - Mat, Johari (Jurnal Usuluddin, 1997)
Ghuluw has been in man's mind since infinite past. It can arise from man's fanatic in certain concepts or on his worship of a personality. Islam forbids Ghuluw because it has potential to destroy faith and society. Ghuluw, which is common in the stance towards godship, prophethood and life after death, has its root in ignorance and limited knowledge, selfishness, adherence to false hadiths, influence of previous religions and tyrany. To avoid Ghuluw, Islam should be understood through its genuine sources with guidances of the Sahabah, Tabien and al-Tabien and the authoritative Imams.